Individual Learning Program As Implementation of Inclusive Education in Integrated PAUD Mutiara Yogyakarta - Hibana, Hibana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to describe and analyze the Individual Learning Program/PPI to formulate a learning process based on an assessment made of student profiles. PPI implementation is expected to optimize the abilities of heterogeneous children in the Mutiara Yogyakarta Integrated PAUD. This research is qualitative research with a field study with a descriptive research type. The data sources used were primary data, namely from teachers and students at the Mutiara Yogyakarta Integrated PAUD, and secondary data from books, journals, magazines, and documentation by this study. The data collection tools for this research were interviews with PAUD teachers, observation of individual learning programs, and documentation of Field Learning Programs. Data analysis was done using the triangulation method by sorting, grouping, and concluding. The research results on the Individual Learning Program implemented at the Mutiara Yogyakarta Integrated PAUD are four: planning, implementation, evaluation, and follow-up. The PPI concept aligns with one of the Pearl Pillars of Integrated PAUD Education, as a Child-Centered. All activity programs are designed based on the needs and conditions of the child, with individual attention. PPI planning is carried out by involving a written agreement with the parents. In this case, parents are involved in program design and implementation.